Answer:
Step-by-step explanation:
Given
Finding (fog)(x)
(fog)(x) = f(g(x))
(fog)(x) = f(x+9)
(fog)(x) = 5(x+9) ∵ substitute x as x+9 in the f(x)
(fog)(x) = 5x+45
Finding (gof)(x)
(gof)(x) = g(f(x))
(gof)(x) = g(5x)
(gof)(x) = 5x+9 ∵ substitute x as 5x in the g(x)
Finding (fog)(3)
(fog)(3) = f(g(3))
substitute x = 3 in the g(x)=x+9
g(x) = x+9
g(3) = 3+9
g(3) = 12
so
(fog)(3) = f(g(3)) = f(12)
now substitute x = 12 in f(x) = 5x
f(x) = 5x
f(12) = 5(12)
f(12) = 60
Thus,
(fog)(3) = f(g(3)) = f(12) = 60